The Principle of Proportionality in Anti-Pornography Law: Comparing Several Countries - Sulistyanta, Sulistyanta; Handayani, I Gusti Ayu Ketut Rachmi; Karjoko, Lego; Danendra, Ravi (Universitas Negeri Semarang, 2023)
The imperative role of anti-pornography laws in shielding the younger generation from the pervasive influence of explicit content is indisputable. Nevertheless, the critique leveled against the formulation of criminal sanctions within the ambit of anti-pornography legislation necessitates a rigorous examination of the principle of proportionality. To elucidate this issue, juridical normative research is paramount, with a particular focus on comparative analyses involving Law No. 44 of 2008 and corresponding anti-pornography statutes in Sweden, the Philippines, Malaysia, and India. The findings derived from this comparative investigation reveal several key insights. Firstly, a nuanced exploration exposes both commonalities and disparities in the patterns underpinning the formulation of anti-pornography statutes across these jurisdictions. Secondly, while there is alignment between the gravity of the offense and the severity of criminal sanctions, a notable deficiency surfaces in the failure to distinguish between first-time offenders and recidivists, thereby falling short of the fundamental principle of proportionality. Furthermore, a critical observation underscores the absence of rehabilitative measures for adult offenders grappling with pornography addiction, presenting a lacuna in the current legislative framework. Lastly, the relative nature of anti-pornography formulations from diverse nations underscores a compelling correlation between the legal stance on criminality and the prevailing moral ethos of the respective societies. This comprehensive analysis serves as a clarion call for a recalibration of anti-pornography legislation, aligning it more closely with the principle of proportionality and accounting for the nuanced considerations in rehabilitating offenders.